The Shifting Dynamics of Madrasah Diniyah ‎Education in Madura: Perspectives on ‎Learning Models and Pesantren Quality - Abd Mukhid; Saiful Hadi; Siswanto; Mohammad Thoha; Jamiludin Usman (TADRIS: Jurnal Pendidikan Islam, 2023)
This study aims to reveal Islamic boarding schools' learning models and quality in the Equality Education Program of Salaf Islamic Boarding Schools in Madura. This study used a qualitative approach with a descriptive research type. The research was conducted in several Islamic boarding schools of Madura island to represent Islamic boarding schools that have implemented the Salaf Islamic Boarding School Equality Education Program. The results of this study indicate that the equality program has been carried out in several Islamic boarding schools in Madura. The implementation of this program is carried out by applying a mixed learning model, namely the conventional learning model (sorogan and bandongan) and the online learning model, through the Equality Test, Computer-Based National Assessment (CBNA), and Computer-Based Education Unit Examination (CBEUE). Quality assurance is implemented by utilizing an internal and external evaluation system. While a particular team from the Ministry of Religion conducts external evaluations, pesantren administrators and managers are responsible for internal evaluations. The shift in madrasah diniyah education shows that pesantren have been able to apply online learning models while maintaining conventional learning models. The quality of pesantren is increasing with the number of students, equalizing students' education with general education, and obtaining formal recognition from the National Accreditation Board for schools/madrasahs.